An investigation on the effects of attitude towards algebraic problem-solving achievement - Samiran Das; Imdad Ali (International Journal of Evaluation and Research in Education (IJERE), 2023)
The main focus of this work is to explore the effects of students’ attitudes towards problem solving (ATPS) in algebra with respect to gender and type of school. The contribution of the predictor variables of ATPS in algebra to the prediction of problem-solving achievement (PSA) is being investigated. For the study, 200 class IX students are randomly selected from the government (GOVT) and private (PVT) schools in the Morrigan district, India. The algebraic attitude scale (AAS) is used to determine students’ ATPS, whereas the problem-solving test (PST) is used to determine students’ PSA in algebra. The AAS instrument consists of three subscales: perseverance (PE); self-confidence (SC), and willingness (WL). The t-test and multiple regression analysis are used to analyze the collected data. The finding reveals that there are statistically significant differences in students’ ATPS based on gender and type of school. The finding also reveals that PE, SC, and WL have a significant positive relationship with the PSA in algebra. Therefore, it is suggested that teachers should make an effort to provide support in the form of explanations, modeling, coaching, and other forms of assistance, as well as a conducive environment that encourages students’ overall ATPS that can enhance their PSA in Mathematics.